COVID 19 AND YOUNG PEOPLE: UNDERSTANDING THE IMPACT - Zorcec, Tatjana; Cepreganova, Tatjana; Zorcec, Danijela (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
COVID-19 has impacted individuals of all age groups, including young people.Although young individuals generally experience milder symptoms and better outcomes, they are still susceptible to contracting and transmitting the virus. While they may have lower infection rates, it is crucial for young people to adhere to preventive measures as they can still spread the virus, potentially affecting vulnerable populations. The pandemic and related measures have also had an impact on the mental health of young people, with increased stress, isolation, and changes in social interactions leading to feelings of anxiety, depression, and loneliness. The closure of schools and the shift to remote learning have presented challenges in terms of education and social development. It is essential for young people to stay informed, follow guidelines, and prioritize their physical and mental well-being during these challenging times. Keywords: pandemic, COVID-19 experience, young people.